PEMANFAATAN ICT CENTER DALAM PENINGKATAN AKSES SUMBER BELAJAR BAGI MAHASISWA UNIVERSITAS TERBUKA - Pardamean Daulay (LPPM Universitas Terbuka, 2009)
To Increasing the learning resources access for UT students is one of the important agenda that needs to be translated into optimizing the role of Unit Program Belajar Jarak Jauh (UPBJJ). In this case, UPBJJ-UT Surabaya has developed a collaboration to utilize ICT Center which related to the National Education Network activity (Jardiknas). This research aim is to describe the use of ICT Center for increasing the access to the learning resources for UT students, by using a qualitative approach and descriptive evaluative research strategy. The result of this research shows that student participation in the ICT Center facility is still low, the only 53 student (11.77%). The low participation of students is due to, (1) lack of adequate socialization to students, (2) students ability to access the internet, (3) location of ICT Center from students resident, and (4) the lack of obligation policy for UT students to access the internet. The results of this research also shows that the collaboration between UPBJJ UT-Surabaya with the ICT Center is not optimal, because of; (1) limited technical guidance, (2) is no clarity of operational cost, and (3) the knowledge ICT Center the UT website. However, the collaboration a good prospect, because of the strong of government to the ICT Center activity.